Masculinidades em trânsito: processos identitários de motoboys em Belo Horizonte MG - Gregorio Ribeiro de Miranda (2015)
Historically recent and still in full ascendancy, the motorcycles boom in our cities meant major changes in daily life and was appropriated in different ways by the population. Situated between leisure and work, the motorcycle couriers have meaningful participation in the elevation of theaccident rates and traffic mortality and share the general profile of motorcyclists in the country: low-income young men. This study investigated, thus, the relationship between the vehicle that kills the most in Brazil the motorcycle and the group that dies the most the young men. In order to contribute to the understanding of the costs and consequences of male socialization within the motorcycling, this work is founded on the Henri Tajfels Social Identity Theory. The study aimed to identify which possibilities of being a man are given for motorcycle couriers in the metropolitan region of Belo Horizonte and how these different versions of masculinity influence how they see and feel themselves and how they behave as bikers. Thereby, we performedten semi-structured interviews with motorcycle couriers residents of the metropolitan region of Belo Horizonte/MG and analyzed them by the content analysis technique. As they located themselves amid the social fabric, respondents seek, in general, (a) a positively valued identity; (b) belongings that contribute with some degree of individuation and (c) references that make possible to them to prove themselves as men. Motorcycle and profession compose, for the respondents, two closely related spheres, intertwined and often confused. From the verybeginning in the profession, the reasons that led them to it, to how they call themselves and identify with each other, it is often tenuous the border between hobby and work. They also demonstrated to share an ideal of the good biker permeated by masculine values: a competent person, responsible, heterosexual, bold, fearless, independent and able to maintain control of the city, his family and his machine. Being a professional biker is a gendered identity. While they recognize to live with many risks in traffic, respondents largely believe that they are invulnerableto them. The dangers to which they are exposed daily are persistently allocated to external spheres: the drivers (irresponsible and violent), to their own motorcycle (which calls for speed) and to the transit in the abstract (a competitive, chaotic and hostile environment). Instead of slow, fearful and followers of rules such as women and amateur bikers, the real biker is agile, careful, dynamic and are not knocked down easily. As someone who knows all the avenues, streets and shortcuts, fully dominates the machine and handles all the tricks, the motorcycle courier knows himself as an authority in motorcycling. The good motorcyclist isnot only a good rider and a good worker, he is an exceptional man.